1980
DOI: 10.1099/00221287-120-2-453
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dissolved Oxygen Tension on the Metabolism of Methylated Amines in Hyphomicrobium X in the Absence and Presence of Nitrate: Evidence for 'Aerobic' Denitrification

Abstract: Hyphomicrobium X possesses two different enzymes for the oxidation of dimethylamine, namely dimethylamine dehydrogenase and dimethylamine mono-oxygenase. During growth of the organism in batch culture at dissolved oxygen tensions (DOT) in excess of 30 mmHg in media containing trimethylamine as the carbon and energy source, dimethylamine mono-oxygenase was the only enzyme involved in dimethylamine oxidation. The apparent K, of the mono-oxygenase for oxygen was relatively high (23-2 ,uM). The enzyme was less sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
4

Year Published

1983
1983
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 14 publications
(25 reference statements)
0
32
0
4
Order By: Relevance
“…When nitrate is present and lo 2 < Co 2 < ho 2 , both aerobic respiration and denitrification occur. Increasing denitrification activity with decreasing oxygen tension in continuous culture studies of Hyphomicrobium X was reported by Meiberg et al (1980). When lc 2 H 2 < Cc 2 H 2 < hc 2 H 2 , the conversion of nitrous oxide to molecular nitrogen, Eq.…”
Section: Denitrification; a Case Studymentioning
confidence: 86%
“…When nitrate is present and lo 2 < Co 2 < ho 2 , both aerobic respiration and denitrification occur. Increasing denitrification activity with decreasing oxygen tension in continuous culture studies of Hyphomicrobium X was reported by Meiberg et al (1980). When lc 2 H 2 < Cc 2 H 2 < hc 2 H 2 , the conversion of nitrous oxide to molecular nitrogen, Eq.…”
Section: Denitrification; a Case Studymentioning
confidence: 86%
“…A second example of denitrification in the presence of low, but significant concentrations of dissolved oxygen was reported by Meiberg et al (1980). They found that with Hyphomicrobium X in chemostat cultures growing on dimethylamine, the induction of the denitrifying enzymes required the presence of nitrate, and also appeared to be linked to the growth rate.…”
Section: Oxygen Initibitionmentioning
confidence: 94%
“…Free-living bacteria usually respire nitrate under anoxic conditions (Payne 1973, Stouthamer 1980, Tiedje 1988, only a few free-living bacteria are known for aerobic denitrification (Krul & Veeningen 1977, Meiberg et al 1980, Robertson & Kuenen 1984a, b, Lloyd et al 1987, Robertson et al 1988 or co-respiration of oxygen and nitrate (Bonin & Gilewicz 1991). These bacteria are denitrification specialists and do not shut down their denitrification enzymes in response to…”
Section: Aerobic Nitrate Respirationmentioning
confidence: 99%